An Integrated Control and Management Approach of Stand-alone Hybrid Wind/PV/Battery Power Generation System with Maximum Power Extraction Capability*. Issue 2 (1st March 2017) - Jayalakshmi, N.S.; Gaonkar, D.N.
ABSTRACT: The production of electricity from renewable energy sources like wind and photovoltaic energy increases in recent years, due to environmental problems and the shortage of traditional energy sources. In this article, a detailed mathematical model and a control scheme for hybrid wind and photovoltaic or PV based DG system, with battery and maximum power extraction capability for isolated mode of operation is developed. The wind power generation system uses wind turbine (WT), a permanent magnet synchronous generator (PMSG), a three-phase diode rectifier bridge, DC/DC boost converter with a Maximum Power Point Tracking or MPPT controller. The PV generation system uses PV array, a boost converter with maximum power point tracking or MPPT controller. Both sources and battery are connected to common dc bus with a dc link capacitor and supply power to load through Pulse Width Modulating (PWM) voltage source inverter. The overall control system consists of MPPT controller for both Wind and PV power system, a bi-directional dc-dc converter controller for battery energy storage management and load side inverter controller for voltage and frequency regulation. Control strategies for individual system components of the proposed system are designed with a view to achieve an acceptable level of voltage and frequency regulation while extracting the maximum power from wind and PV system. The performance of the developed hybrid system is investigated in terms of voltage and frequency regulation capability under changing wind, solar irradiation and variable load conditions.